Review and Assessment of Medicinal Safety Data of Orally Used Echinacea Preparations - Ardjomand-Woelkart, Karin; Bauer, Rudolf (Planta Medica, 2016)
Echinacea purpurea, Echinacea angustifoli and Echinacea pallida are frequently used as medicinal plants. Besides asking for evidence on their efficacy, there is an increasing interest for safety data. This review systematically presents the available literature on drug interactions, contraindications, adverse events, duration of use, and safety of use in pregnant and nursing women, and assesses the safety profile of corresponding Echinacea preparations. It is noteworthy that all safety data reported are as product specific as the pharmacological or efficacy data are. In pharmacokinetic herb-drug interaction studies performed in vivo, no significant inhibitions of human CYP2D6 and CYP3A4 isoforms have been found after the administration of standardized E. purpurea preparations. However, contradictory results exist in studies using liver microsomes. Adverse events reported during clinical trials following administration of Echinacea spp. mono-preparations were generally mild and mostly without causality. Due to published long term studies with continuous ingestion of different Echinacea preparations up to 6 month with no reported toxicological concerns, Echinacea can be recommended also for long-term use. Moreover, the contraindications in cases of autoimmune diseases and immune-suppression are questionable, since lipophilic Echinacea preparations containing alkamides suppress cellular immune responses, and beneficial effects in autoimmunity were reported. The same applies for the use during pregnancy. Although there has been some impact reported on embryonic angiogenesis in mice, no association with an increased risk for major or minor malformations during organogenesis was found in a literature review. Altogether, the different evaluated Echinacea preparations are well-tolerated herbal medicines in the management in children and adults alike.
Keywords: Echinacea spp.; Asteraceae; safety